Legal Implications in Breaching Patient Confidentiality through Social Networks - Jahn Kassim, Puteri Nemie (2012)
The popularity of social networks has grown rapidly in recent years. There is a widespread use of sites such as Facebook and Twitter amongst medical students and doctors without knowing the potential risks that may arise. Disclosing identifiable information about patients without consent on blogs, medical forums or social networking sites would constitute a breach of legal and ethical duty of confidentiality and could give rise to defamatory actions by the patients.